A Low Cost Cabinet Type Seed Germinator - Gupta, B. N.; Kumar, Adarsh (Indian Forester, 1977)
The article describes the cabinet type seed germinator designed and fabricated in the Seed Testing Laboratory of the Forest Research Institute. Dehra Dan, India. The germinator has been tested for its performance and found and satisfactory for use throughout the year from room temperature to 45°C (± 1°C).